The 4G/5G Genetic Polymorphism in the Promoter of the Plasminogen Activator Inhibitor-1 (PAI-1) Gene Is Associated with Differences in Plasma PAI-1 Activity but not with Risk of Myocardial Infarction in the ECTIM Study - Ye, S; Green, F R; Scarabin, P Y; Nicaud, V; Bara, L; Dawson, S J; Humphries, S E; Evans, A; Luc, G; Cambou, J P; Arveiler, D; Henney, A M; Cambien, F (Thrombosis and Haemostasis, 1995)
We have investigated the interrelationships of plasma PAI-1 activity, the PAI-1 4G/5G polymorphism and risk of myocardial infarction (MI) in the ECTIM study, a case-control study of MI based in Belfast, Lille, Strasbourg and Toulouse. Mean PAI-1 levels in cases were similar across all centres but in controls, levels in the French centres were significantly higher. Only in Belfast were PAI-1 levels higher in cases (11.7AU/ml) than controls (10.5AU/ml). The PAI-1 4G allele frequency was similar in cases and controls (0.55 and 0.54). In all groups, 4G homozygotes had the highest mean plasma PAI-1 level (4G4G vs 5G5G; cases overall: 14.2 vs 12.1 AU/ml; controls overall: 15.0 vs 12.6AU/ml), with the heterozygotes generally intermediate. The data from Belfast are consistent with the literature implicating PAI-1 level as an MI risk factor. In ECTIM, the PAI-1 4G/5G polymorphism is not a genetic risk factor for MI but is associated with PAI-1 activity. Thus homozygosity for the 4G allele may predispose to elevated PAI-1 and impaired fibrinolysis, perhaps requiring interaction with other genetic or environmental factors to influence MI risk.